Determination of the relationship between internal auditory canal nerves and tinnitus based on the findings of brain magnetic resonance imaging - Ergen, Burhan; Baykara, Murat; Polat, Cahit (Elsevier Sci Ltd, 2018)
This experimental study aimed to investigate a relationship between tinnitus and thicknesses of internal auditory canal and nerves in it. It was performed on brain magnetic resonance images of patients who consulted the ear, nose, and throat clinic with tinnitus complaint. Statistical hypothesis tests and classification experiments were performed on these data to find out structural differences in internal auditory channel components in patients with tinnitus after obtaining cross-sectional areas of nerves as thicknesses. Both the hypothesis tests and classification results showed that the thicknesses of nerves in tinnitus cases were different from those in normal cases. In particular, the hypothesis tests for the superior vestibular nerve and internal auditory channel showed the highest significance, indicating the relationship with tinnitus. The classification results indicated the possibility of classification for tinnitus identification, establishing a computer-assisted diagnostic system to help physicians. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Extreme learning machine; Internal auditory canal; Statistical significance; Tinnitus